Elevated Levels of IL-27 Are Associated with Disease Activity in Patients with Crohn's Disease. (26th October 2021) - Cui, Xiufang; Jiao, Chunhua; Wang, Di; Ye, Ziping; Ma, Jingjing; Tang, Nana; Zhang, Hongjie
Abstract : Immune disorders play an important role in the pathogenesis of Crohn's disease (CD). Notably, the increased immune response of Th1 cells and related cytokines is associated with the onset of CD. IL-27 is a newly discovered IL-12-related cytokine, but its expression and clinical significance in CD patients are still controversial. This study is aimed at evaluating the serum levels of IL-27 in CD patients and analyzing their clinical significance. The results indicated that serum levels of IL-27 in CD patients were significantly higher than those in control subjects (median (interquartile range (IQR)): 110.0 (95.0, 145.0) vs. 85.0 (80.0, 95.0) pg/ml, P < 0.001 ). Furthermore, the IL-27 levels significantly increased in CD patients at the active stage compared with CD patients in remission (CDR) (127.5 (100.0, 150.0) vs. 90 (80.0, 110.0) pg/ml, P < 0.001 ). However, there was no difference in IL-27 levels between CDR and control subjects. The levels of IL-27 were positively correlated with Crohn's disease activity index (CDAI), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), fecal calprotectin (FC), and Simple Endoscopic Score for Crohn's Disease (SES-CD) and negatively correlated with hemoglobin (Hb) and serum albumin (ALB). IL-27 combined with CRP favored the prediction of CD activity (area under the curve (AUC): 0.88). Additionally, the proportions of Th17 and Th1 cells in peripheral blood were higher in CD patients than in control subjects. Active CD patients exhibited significantly higher proportions of Th17 and Th1 cells than those in remission. Moreover, correlation analysis indicated that the serum levels of IL-27 were positively associated with the frequency of Th17 cells in CD patients (r = 0.519, P = 0.013 ) but not associated with the frequency of Th1 cells in CD patients. IL-27 is positively associated with multiple inflammation indicators and may exert a proinflammatory profile by regulating Th17 cell differentiation in the development of Crohn's disease. In the future, IL-27 combined with CRP is expected to become an important biological marker of CD activity.